Use Of Agricultural Land In The Highway Protection Zone - Ibrokhimov Saidmukhammad Saidkamol ogli (Genius Journals, 2024)
The article is focused on the use of agricultural lands in protected zones of highways. Legislative restrictions aimed at protecting road infrastructure and ensuring traffic safety are considered. Particular attention is paid to the need for a balance between the development of transport infrastructure and the rational use of agricultural land.
Keywords: agricultural land; protected zone; highways